GASTRODIPLOMASI THAILAND SEBAGAI NATION BRANDING DALAM MEMPENGARUHI JUMLAH WISATAWAN ASING TAHUN 2017-2019 - Amelia Chaerani (2022)
Thailand as a country that was previously known as a country that has a bad image in the eyes of the international community slowly wants to change its image to a more positive one. With that, the Thai government carried out a strategy by carrying out a gastrodiplomacy program as an effort to form a new image for the country of Thailand. With Thailand's popularity as a country that has a positive image and is known for its food, this has become one of the factors for the increasing number of foreign tourists in Thailand in 2017-2019. This study aims to find out how Thailand's efforts to carry out gastrodiplomacy form a new image for Thailand. The research method used in this research is descriptive qualitative and uses primary and secondary data. Data collection techniques are using interview techniques and literature or literature studies. The final result of this research is Thailand's efforts to establish a gastrodiplomacy program so that Thai food can be known in the eyes of the international community so that it can be one factor in the increasing number of foreign tourists who come in 2017-2019. Keywords: Gastrodiplomacy, Nation Branding, Tourism, Culinary, Culture